HUBUNGAN PERAN PETUGAS KESEHATAN DAN PROMOSI SUSU FORMULA DALAM PEMBERIAN ASI EKSKLUSIF PADA IBU MENYUSUIDI WILAYAH KERJA PUSKESMAS HARAPAN RAYA - Armoni Suci Dewi; Ayu Gustiwarni; Rika Sri Wahyuni (LPPM Universitas Muhammadiyah Riau, 2019)
Exclusive breastfeeding is breastfeeding alone for the first 6 months of life without any additional fluids such as formula, oranges, honey, water and without additional solid foods such as bananas, milk porridge, biscuits. Factors affecting the success and failure of exclusive breastfeeding is one of them is the role of health officers and the promotion of infant formula. This study aims to determine the relationship between the role of health officers and the promotion of formula milk to exclusive breastfeeding in breastfeeding mothers in the Work Area of ​​Harapan Raya Pekanbaru Health Center Year 2018. The research type is quantitative and analytic design with cross sectional approach. The study was conducted in Harapan Raya Public Health Working Area in March - April of 2018. The population of this study is all mothers who have infants aged 6-12 months in Harapan Raya Pekanbaru Health Center Working Area as many as 2,494 people, the sample of 96 respondents with quota sampling method sampling. The instrument of this research using questionnaires and techniques of this study using primary data and secondary data. Based on the result of the research, the mother who has babies in the work area of ​​Harapan Raya Pekanbaru Minority Health Center gave exclusive breast feeding of 47 (49%) and got the health worker role 35 (36,5%) and did not get formula promotion equal to 36 (37,5 %). so it can be concluded there is no relation between the role of health officer to exclusive breastfeeding (P Value 0,563) and there is relationship between promotion of formula milk to Exclusive Breast Feeding (P Value 0,040). It is hoped for health workers to further improve the provision of information on Exclusive Breast Milk and its benefits by providing counseling or other approaches.